2019
DOI: 10.1002/advs.201802109
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Detection Methods in Photocatalytic and Electrocatalytic Experiments: How to Improve the Reliability of NH3 Production Rates?

Abstract: The enzyme nitrogenase inspires the development of novel photocatalytic and electrocatalytic systems that can drive nitrogen reduction with water under similar low‐temperature and low‐pressure conditions. While photocatalytic and electrocatalytic N 2 fixation are emerging as hot new areas of fundamental and applied research, serious concerns exist regarding the accuracy of current methods used for ammonia detection and quantification. In most studies, the ammonia yields are low and littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
372
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 441 publications
(424 citation statements)
references
References 29 publications
8
372
0
2
Order By: Relevance
“…To explore the role of Vo and electron‐rich Cu δ + in promoting photocatalytic reactions, we evaluated the performance of X ‐ZnAl‐LDH and the various reference photocatalysts (ZnAl‐LDH and CuZnAl‐LDH) for photocatalytic nitrogen fixation under UV–vis irradiation ( Figure 3 a). The photocatalytic activity of all samples was assessed in N 2 ‐saturated water under UV–vis (Xe lamp) irradiation at ambient temperature and pressure, using ion chromatography for accurate ammonia quantification . As shown in Figure b, all the LDH samples were active for photocatalytic N 2 fixation, with the rates of ammonia production following the order: 0.5%‐ZnAl‐LDH (110 µmol g −1 h −1 ) > 1%‐ZnAl‐LDH (50 µmol g −1 h −1 ) > 0.25%‐ZnAl‐LDH (42.6 µmol g −1 h −1 ) > 3%‐ZnAl‐LDH (37.6 µmol g −1 h −1 ) > CuZnAl‐LDH (31.1 µmol g −1 h −1 ) > ZnAl‐LDH (17.1 µmol g −1 h −1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To explore the role of Vo and electron‐rich Cu δ + in promoting photocatalytic reactions, we evaluated the performance of X ‐ZnAl‐LDH and the various reference photocatalysts (ZnAl‐LDH and CuZnAl‐LDH) for photocatalytic nitrogen fixation under UV–vis irradiation ( Figure 3 a). The photocatalytic activity of all samples was assessed in N 2 ‐saturated water under UV–vis (Xe lamp) irradiation at ambient temperature and pressure, using ion chromatography for accurate ammonia quantification . As shown in Figure b, all the LDH samples were active for photocatalytic N 2 fixation, with the rates of ammonia production following the order: 0.5%‐ZnAl‐LDH (110 µmol g −1 h −1 ) > 1%‐ZnAl‐LDH (50 µmol g −1 h −1 ) > 0.25%‐ZnAl‐LDH (42.6 µmol g −1 h −1 ) > 3%‐ZnAl‐LDH (37.6 µmol g −1 h −1 ) > CuZnAl‐LDH (31.1 µmol g −1 h −1 ) > ZnAl‐LDH (17.1 µmol g −1 h −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…To confirm that the NH 3 detected in this study was generated by direct N 2 photofixation, as opposed to arising from other sources, isotope labeling experiments using 15 N 2 and various control experiments were performed. When 15 N 2 was used as the feed gas, the products of 15 NH 4 + can be detected using the indophenol blue method coupled with high‐resolution mass spectroscopy (Figure e). The obtained indophenol products containing 15 N and 14 N gave characteristic mass spectrometry signals at m / z 199 and m / z 198, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…As an alternative, the spectrophotometric method is the most popular means for ammonia detection. Recently, systematic investigations on the effect of pH, metal ion interference, sacrifice agents, and nitrogen‐containing chemicals on the ion chromatography, indophenol blue and Nessler's reagent methods have been carried out by Zhao et al Through a direct comparison of standard curves for ammonia determined by these methods, the authors provided the following suggestions. When the produced NH 3 concentration was lower than 500 µg L −1 , these three detection methods demonstrated similar results.…”
Section: Reaction Systems Of Electrochemical and Photoelectrochemicalmentioning
confidence: 99%
“…Consequently, overestimation and significant errors in ammonia quantification have been noticed. Recently, Zhao et al . reported a systematic investigation regarding the interference effect of coexisting metal cations and organic compounds on the quantification method and concluded that the results by the spectrophotometric method are easy to be interfered in the complex matrixes.…”
Section: Introductionmentioning
confidence: 99%